2010
DOI: 10.1158/1940-6207.capr-09-0202
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of Cigarette Smoke–Induced Alterations of MicroRNA Expression in Rat Lungs

Abstract: We previously showed that exposure to environmental cigarette smoke (ECS) for 28 days causes extensive downregulation of microRNA expression in the lungs of rats, resulting in the overexpression of multiple genes and proteins. In the present study, we evaluated by microarray the expression of 484 microRNAs in the lungs of either ECS-free or ECS-exposed rats treated with the orally administered chemopreventive agents N-acetylcysteine, oltipraz, indole-3-carbinol, 5,6-benzoflavone, and phenethyl isothiocyanate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 46 publications
4
100
0
Order By: Relevance
“…Administration of the dietary agents, Phenethyl isothiocyanate (PEITC) and Indole-3-carbinol (I3C), two major components of cruciferous vegetables, attenuated the cigarette smokeinduced down-regulation of miRNA expression. In the case of the combined treatment with PEITC and I3C, they had profound effects on almost all CS-down-regulated miRNAs and their expression even exceeded the baseline situation (59). In previous studies, PEITC was also the most effective agent in inhibition of CS-related cytogenetic damage, transcriptome alterations, and lung tumorigenesis (55,60,61).…”
Section: Anti-estrogenic Compounds As Attenuators Of Cigarette Smoke mentioning
confidence: 86%
“…Administration of the dietary agents, Phenethyl isothiocyanate (PEITC) and Indole-3-carbinol (I3C), two major components of cruciferous vegetables, attenuated the cigarette smokeinduced down-regulation of miRNA expression. In the case of the combined treatment with PEITC and I3C, they had profound effects on almost all CS-down-regulated miRNAs and their expression even exceeded the baseline situation (59). In previous studies, PEITC was also the most effective agent in inhibition of CS-related cytogenetic damage, transcriptome alterations, and lung tumorigenesis (55,60,61).…”
Section: Anti-estrogenic Compounds As Attenuators Of Cigarette Smoke mentioning
confidence: 86%
“…Among them, the upregulated miRs included let-7a, let-7b and let-7c (23). Izzotti et al (27,28) found that exposure to cigarette smoke alters miR expression in the lungs of rats. Our study demonstrated that expression of the tumor suppressors let-7a/7g was upregulated after tea catechin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been reported that tea catechins induce the modification of the expression profile of miRs and mediate the apoptotic effect in human cancer cells (22,23). Furthermore, let-7 is known as a tumor suppressor in lung cancer cells or animal models by repressing cell proliferation (10,(24)(25)(26) and its expression profile may be altered by various agents (23,27,28). However, the effect and mechanism of tea catechins on let-7 expression in human lung cancer remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…miR125b, miR-26a, miR-146-pre, let-7a, let-7c, miR-192, miR-222-pre, miR-99, and miR-123 are some of the miRNA downregulated by cigarette smoke; their expression was altered in rats treated with orally administered PEITC for 3 days prior to exposing them to cigarette smoke for 28 consecutive days (84). The effect of PEITC or glucocorticoid budesonide treatment, either alone or in combination, on miRNA expression was analyzed in the mouse liver and lungs.…”
Section: Phenethyl Isothiocyanatementioning
confidence: 99%